2022
DOI: 10.1002/lary.30078
|View full text |Cite
|
Sign up to set email alerts
|

Neuroradiological Basis of COVID‐19 Olfactory Dysfunction: A Systematic Review and Meta‐Analysis

Abstract: Objective Olfactory dysfunction (OD) is a common presenting symptom of COVID‐19 infection. Radiological imaging of the olfactory structures in patients with COVID‐19 and OD can potentially shed light on its pathogenesis, and guide clinicians in prognostication and intervention. Methods PubMed, Embase, Cochrane, SCOPUS were searched from inception to August 1, 2021. Three reviewers selected observational studies, case series, and case reports reporting radiological changes in the olfactory structures, detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 73 publications
(260 reference statements)
0
32
0
Order By: Relevance
“…Sensorineural mechanisms are currently thought to be the predominant mechanism of covid-19 related smell dysfunction, 54 55 although conductive mechanisms have been implicated too. 56 SARS-CoV-2 infects and eliminates most olfactory epithelial support (sustentacular) cells that express angiotensin converting enzyme-2, which leads to olfactory neuron deciliation and necrosis. 55 57 Varying regeneration speed of support cells and sensory neurons, influenced by the degree of inflammation, could explain the delayed smell recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Sensorineural mechanisms are currently thought to be the predominant mechanism of covid-19 related smell dysfunction, 54 55 although conductive mechanisms have been implicated too. 56 SARS-CoV-2 infects and eliminates most olfactory epithelial support (sustentacular) cells that express angiotensin converting enzyme-2, which leads to olfactory neuron deciliation and necrosis. 55 57 Varying regeneration speed of support cells and sensory neurons, influenced by the degree of inflammation, could explain the delayed smell recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased T2 FLAIR signal intensity of OB has been detected in COVID-19-related OD compared to non-COVID-19 anosmic controls by a recent study [ 29 ]. A recent meta-analysis showed that 88% of patients with OD due to COVID-19 had signal abnormalities in OB, which were not significantly different from controls (94%) [ 9 ]. It can be speculated that diversity in the results stems from the methodological differences in the studies, especially the applied field of strength and the time of imaging regarding the disease phase [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the high presence of ACE2 and TMPRSS2 in the OC region, especially supporting (sustentacular) cells of the olfactory epithelium rather than olfactory neurons [ 10 ]. A recent systematic review of 30 studies showed a pooled prevalence of 63% (95% CI, 0.38 to 0.82) for OC opacification in CT or MR imaging of COVID-19 patients with OD, which was significantly higher than the controls with 4% (95% CI, 0.01 to 0.13) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, smell and taste loss are common complaints among patients with covid-19, with an estimated 50% of patients reporting these symptoms 1. This is thought to occur due to conductive barriers and nerve damage from the extensive inflammation in covid-19 infection 2345…”
mentioning
confidence: 99%